Reliability of the Lymph Node Ratio in the Prediction of Gastric Cancer Survival - Kamalı, Sedat; Ulusoy, Cemal; Kamalı, Gülçin Harman (Lietuvos chirurgija, 2023)
Background. Lymph node metastasis is the major determinant factor in the prognosis of gastric cancer. There is still no definite consensus on the lymph node number that should be harvested during gastric cancer surgery. Lymph Node Ratio (LNR) is defined as the ratio of metastatic nodes to the total number of pathologically examined lymph nodes. LNR has been proposed to be a sensitive prognostic factor in patients with gastric cancer. In this study the reliability of the LNR is tested for being a prognostic factor in gastric cancer survival. Methods. Medical records of 244 patients, with neither distant metastases nor neoadjuvant treatment underwent curative gastrectomy, were analyzed retrospectively in terms of survival according to the lymph node ratio (LNR). Patients were divided in two groups by using LNR cut-off value. Results. LNR of 0.4 was proved to be the best cut-off value to predict the prognosis of patients with gastric cancer. Univariate and multivariate analysis revealed that age over 65 (p < 0.001), and LNR ≥ 0.4 (p = 0.02) were independent factors in gastric cancer survival. Patients with LNR ≥ 0.4 presented with worse outcomes regarding other prognostic parameters (tumor differentiation, tumor diameter, lymphovascular invasion or perineural invasion), despite similar numbers of lymph nodes being harvested in both groups during surgery. Conclusion. Lymph node ratio is a reliable parameter to predict the survival in gastric cancer.